Contribuições dos Espaços não Formais para a Educação Ambiental da Escola do Campo no Município de Wanderlândia, TO - SILVA, Patrícia Carneiro da (2024)
The present work aims to identify the practices and discourses about Environmental Education as well as to verify the conceptions of the environment present in the Political Pedagogical Project; analyze the concept of Environmental Education as a cross-cutting theme in the view of rural school teachers; understand the relationship between content and contextualization in the student's daily life, establishing links with meaningful learning in the view of David Paul Ausubel and Paulo Freire; describe which formal spaces are used by teachers and which methodologies are applied, in addition to developing a manual of practical activities related to Environmental Education in the context of a rural school located in the municipality of Wanderlândia, TO. The study was characterized as a qualitative exploratory research carried out along the lines of a case study, as a collection instrument the documentary analysis of the PPP was used and a semi-structured questionnaire was applied to ten teachers assigned to the analyzed teaching unit; the methodology was based on content analysis. Four distinct characterizations of the environment were verified in the Political Pedagogical Project, they are: environment and nature conservation; environment and health; environment and community and environment and resources; it was found that the teachers of the rural school still have a traditional and conservationist view on Environmental Education relating it exclusively to the processes of conservation and nature preservation. That teachers perceive rural education as a public policy that aims at valuing the rural environment and uses the contextualization process to insert the syllabus in the reality experienced by rural people, reflecting on the pedagogical practice of effective learning meaning, which goes against the theory of meaningful learning advocated by David Paul Ausubel and characterized by the pedagogy of freedom taking into account the empirical knowledge experienced by students as a starting point for democratic, effective and equality learning advocated by Paulo Freire. In this context, teachers of the rural school believe that transdisciplinary in Environmental Education can be achieved through the association between the theory of school syllabus and the daily life of rural students, involving all subjects in a contextualized way through studies and projects educational pedagogies, with the deficiency of physical and pedagogical structures being the main obstacles faced for carrying out activities within the scope of Environmental Education in the reality of the rural school